Studi Kandungan Hara Organik dan Anorganik pada Pupuk Organik Berbasis Fermentasi Bakteri dan Biokonversi oleh Cacing Tanah (Vermikompos) - Nurfiansyah, Nurfiansyah; Muhammad Anshar; Ahmad Nurul Muttaqin; Ahmad Zubair Sultan; Mahirullah Mahirullah; Muhammad Arham Yunus (Venn: Journal of Sustainable Innovation on Education, Mathematics and Natural Sciences, 2026)
The increasing accumulation of household organic waste, particularly leaf waste, poses environmental challenges due to limited optimal management and low added value utilization. Leaf waste have potential to be converted into organic fertilizer; however, natural decomposition is slow and often produces compost with inconsistent chemical quality. This study aims to evaluate the organic and inorganic compound content of solid organic fertilizer produced through an integrated approach combining mechanical shredding, bacterial fermentation, and vermicomposting. The research method involved shredding leaf waste using a rotary cutter shredder, followed by bacterial fermentation using activated effective microorganism and subsequent vermicomposting employing Pheretima posthuma. Compost quality was assessed based on physical parameters (temperature, odor, and color) and chemical parameters in accordance with SNI 19-7030-2004. The results showed that the compost reached a relatively mature condition, indicated by stable temperature, earthy odor, and dark brown color at the end of the process. Most chemical parameters met the SNI requirements, particularly phosphorus (P₂O₅) and potassium (K₂O), while heavy metal contents such as Pb and As were not detected and other metals remained well below permissible limits, suggesting the role of earthworm activity in reducing metal bioavailability. However, C-organic content and C/N ratio were slightly below and above the standard range, respectively. Overall, the integrated fermentation–vermicomposting approach demonstrates strong potential as sustainable technology for converting leaf waste into environmentally friendly organic fertilizer. However, further process optimization is required to improve the chemical quality of the product and to enhance the worm separation system for more efficient processing.